Nest architecture of the leaf-cutting ant Acromyrmex rugosus rugosus - Verza, S. S.; Forti, Luiz Carlos [UNESP]; Lopes, J. F. S.; Hughes, W. O. H. (Birkhauser Verlag Ag, 2007)
The prominent nests mounds of many ant species are one of the most obvious signs of their presence, yet the subterranean architecture of nests is often poorly known. The present work aimed to establish the external and internal structure of nests of a species of leaf-cutting ant, Acromyrmex rugosus rugosus, by either marking the interior of nests with talcum powder, or forming casts with cement. Twelve nests were excavated and surveyed, with eight being marked with talcum powder and four cast with cement. The external and internal structure of the nests was highly variable. The largest and smallest nests had mound areas of 9.89 m(2) and 0.01 m(2) respectively. The number of chambers found ranged from I to 26, with maximum dimensions of between 6 and 70 cm. Chambers were found close to the soil surface (6 cm) down to a maximum depth of 3.75 m. In addition to chambers containing fungus garden, some chambers were found to be empty, filled with soil or filled with waste, the first time this has been recorded in a species of Acromyrmex. The nests of A. rugosus rugosus appear to be unusually complex for the genus, containing a diversity of irregular chambers and tunnels.
Keywords: attini; waste management; nest cast; myrmecophiles